2015
DOI: 10.2109/jcersj2.123.1004
|View full text |Cite
|
Sign up to set email alerts
|

The effect of different solid phases on the pyroplastic deformation of porcelain

Abstract: A study on the effect of different minerals on the pyroplastic deformation of ceramic samples was carried out in a muffle furnace. For fair comparison, samples with same chemical composition were used. The mixtures with different minerals were pressed into rectangular bar and placed on alumina supports in the furnace. The green bodies were heated up to their desired temperature and stabilized for 2 h. The solid phases in the sample which were introduced by different raw materials were found to be responsible t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 29 publications
0
16
0
Order By: Relevance
“…The flexural strength reaches its maximum until 1185°C, while found to decrease at higher temperature. The reason could be due to the melting of low-temperature eutectic mixture in iron ore and tailings, as well as the feldspar at about 1100°C, diffuse through the porous matrix causing the pores to plug thereby increasing the bulk density [21]. At a temperature of 1200°C, all the components in addition to low-temperature eutectic mixture began to melt reducing the properties.…”
Section: Thermal Conductivity Of the Samplesmentioning
confidence: 99%
“…The flexural strength reaches its maximum until 1185°C, while found to decrease at higher temperature. The reason could be due to the melting of low-temperature eutectic mixture in iron ore and tailings, as well as the feldspar at about 1100°C, diffuse through the porous matrix causing the pores to plug thereby increasing the bulk density [21]. At a temperature of 1200°C, all the components in addition to low-temperature eutectic mixture began to melt reducing the properties.…”
Section: Thermal Conductivity Of the Samplesmentioning
confidence: 99%
“…However, the short column shaped phases agglomerate around pores and those phases were already identified as mullite phases. 19) Some quartz phases exist in the glassy phase. Figure 7 shows the SEM image (both secondary electron and back scattered electron images) and element mappings in the area of the sample R3 fracture.…”
Section: Phase Composition and Microstructure Of The Samplesmentioning
confidence: 99%
“…Fly ash powders contain mullite crystal nuclei and some of the mullite nuclei locate on the surface of those floaters. 19) With the temperature rising, the nuclei start to grow and form as long strips. At around 1000°C, the liquid phase starts to generate.…”
Section: Densification Mechanismmentioning
confidence: 99%
See 1 more Smart Citation
“…10) Deng et al reported the effect of the distribution of mullite in the glass matrix on pyroplastic deformation. 11) Other studies revealed that the dissolution of quartz in the melt resulted in increasing the viscosity of the liquid phase, thus, reducing the pyroplastic deformation. 12)14) These studies mainly focused on the viscosity of the liquid phase or mullite phase formation in the glass matrix.…”
mentioning
confidence: 99%